Café Scientifique. (1st September 2014) - Grand, Ann
Every month, in 700 or so bars, cafés, pubs, teahouses, shopping centres, community halls, art galleries, libraries, theatres, museums, bookshops ... and a blood donation centre, 40 or so people meet to have a conversation. A conversation that happens to be about science and technology, rather than soap operas or football; this is Café Scientifique.